2019
DOI: 10.1111/vcp.12805
|View full text |Cite
|
Sign up to set email alerts
|

The role of the multi‐drug resistance 1, p53, b cell lymphoma 2, and bcl 2‐associated X genes in the biologic behavior and chemotherapeutic resistance of canine transmissible venereal tumors

Abstract: BackgroundCanine transmissible venereal tumors (CTVTs) generally have different cytomorphologic subtypes and phases of progression. Some tumors have variable biologic behavior including a progressive increase in tumor aggressiveness and variable responses to chemotherapy. This behavior is partially due to high p‐glycoprotein expression by tumor cells, which leads to the expulsion of chemotherapeutic drugs. Other possible causes include changes in pro‐ and anti‐apoptotic genes from the BCL‐2 family and DNA repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
0
9
0
2
Order By: Relevance
“…The protein X associated with BCL2 (Bax) is a proapoptotic protein that triggers mitochondrial membrane permeability in response to apoptotic stimuli. In contrast, Bcl-2 is an anti-apoptotic protein that protects cell death (Alzate et al, 2019). In the antiapoptotic effect of Bcl-2, it is important to stabilize the mitochondrial membrane and prevent the release of cytochrome-c (Lokesh et al;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein X associated with BCL2 (Bax) is a proapoptotic protein that triggers mitochondrial membrane permeability in response to apoptotic stimuli. In contrast, Bcl-2 is an anti-apoptotic protein that protects cell death (Alzate et al, 2019). In the antiapoptotic effect of Bcl-2, it is important to stabilize the mitochondrial membrane and prevent the release of cytochrome-c (Lokesh et al;.…”
Section: Discussionmentioning
confidence: 99%
“…Once the tumor has settled, it can proliferate and spread to other locations in the body and eventually become metastatic. (Alzate et. al., 2019).…”
mentioning
confidence: 99%
“…To date, in CTVT, there have been no reports on BCL-xL expression; however, BCL-2 expression has been identified, as well as mutations in TP53 (CHOI & KIM, 2002;VÁZQUEZ-MOTA et al, 2008;ALZATE et al, 2009;STOCKMANN et al, 2011;FLÓREZ et al, 2017). However; although, there is evidence of mutations of the TP53 gene in CTVT, the ability of this mutation to cause functional changes in the protein, as well as in the tumor evolution remains unknown (VÁZQUEZ-MOTA et al, 2008).…”
Section: Clinic and Surgerymentioning
confidence: 99%
“…Tumor growth is inseparable from sustained and extensive angiogenesis, and inhibition of neovascularization of tumors may be an effective method for treating tumors (27). As the expression of VEGF is closely associated with angiogenesis and tumor cell proliferation, inhibiting and blocking the biological activity of VEGF secreted by tumor cells is important for suppressing tumor growth and metastasis (28).…”
Section: Introductionmentioning
confidence: 99%
“…Bcl-2 activation and abnormal expression is associated with the occurrence and development of tumors ( 27 ). It also plays an important role in the formation of multidrug resistance in tumors ( 28 ). Numerous studies have confirmed that the Bcl-2 gene is closely associated with the occurrence of a variety of malignant tumors ( 29 31 ).…”
Section: Introductionmentioning
confidence: 99%